Proteomic and Biochemical Comparison of the Cellular Interaction Partners of Human VPS33A and VPS33B. Issue 14 (6th July 2018) - Hunter, Morag R.; Hesketh, Geoffrey G.; Benedyk, Tomasz H.; Gingras, Anne-Claude; Graham, Stephen C.
Abstract: Multi-subunit tethering complexes control membrane fusion events in eukaryotic cells. Class C core vacuole/endosome tethering (CORVET) and homotypic fusion and vacuole protein sorting (HOPS) are two such complexes, both containing the Sec1/Munc18 protein subunit VPS33A. Metazoans additionally possess VPS33B, which has considerable sequence similarity to VPS33A but does not integrate into CORVET or HOPS complexes and instead stably interacts with VIPAR. It has been recently suggested that VPS33B and VIPAR comprise two subunits of a novel multi-subunit tethering complex (named "CHEVI"), perhaps analogous in configuration to CORVET and HOPS. We utilized the BioID proximity biotinylation assay to compare and contrast the interactomes of VPS33A and VPS33B. Overall, few proteins were identified as associating with both VPS33A and VPS33B, suggesting that these proteins have distinct sub-cellular localizations. Consistent with previous reports, we observed that VPS33A was co-localized with many components of class III phosphatidylinositol 3-kinase (PI3KC3) complexes: PIK3C3, PIK3R4, NRBF2, UVRAG and RUBICON. Although VPS33A clearly co-localized with several subunits of CORVET and HOPS in this assay, no proteins with the canonical CORVET/HOPS domain architecture were found to co-localize with VPS33B. Instead, we identified that VPS33B interacts directly with CCDC22, a member of the CCC complex. CCDC22 does not co-fractionate with VPS33B and VIPAR in gel filtration of human cell lysates, suggesting that CCDC22 interacts transiently with VPS33B/VIPAR rather than forming a stable complex with these proteins in cells. We also observed that the protein complex containing VPS33B and VIPAR is considerably smaller than CORVET/HOPS, suggesting that the CHEVI complex comprises just VPS33B and VIPAR. Graphical abstract: Unlabelled Image Highlights: VPS33A and VPS33B co-localize with distinct sets of cellular proteins. VPS33A co-localizes with PI3KC3 complex members. VPS33B interacts directly with CCDC22, a member of the CCC complex. VPS33B and VIPAR do not assemble into a larger stable multi-subunit tethering complex.